Case Report: 40Hz multi-target transcranial alternating current stimulation combined with rehabilitation for post-stroke cognitive impairment - Lai, Ming Hui; Wang, Yi Fan; Lu, Yan; Fu, Wang; Zhang, En Bang; Ma, Hong Li; Shan, Chun Lei; Wang, Feng; Huang, Shang Jun; Wang, Cong; Yu, Xiao Ming (Frontiers in Psychiatry, 2025)
40Hz transcranial alternating current stimulation (tACS) has gained attention in cognitive rehabilitation due to its potential to modulate neural oscillations and enhance synaptic plasticity. Most previous studies have focused on single-target stimulation, but post-stroke cognitive impairment (PSCI) involves dysfunction across multiple brain networks. Therefore, multi-target synchronous intervention may offer greater benefits. This case report presents the results of a patient with PSCI who underwent a combined intervention of 40Hz multi-target tACS concurrently with intensive cognitive rehabilitation. The tACS targeted the dorsolateral prefrontal cortex (DLPFC), primary motor cortex (M1), and supplementary motor area (SMA), to address PSCI. Cognitive scales (MOCA; Trail Making Test-A(TMT-A); Clock Drawing Test; Digit Span Test), sequential reaction time task (SRTT) combined with EEG, transcranial magnetic stimulation (TMS), and magnetic resonance imaging (MRI) were used to evaluate the effects of the intervention. After two weeks of the combined treatment, the patient’s MoCA score improved by 10 points, and the completion time for both TMT-A and B and the reaction time of SRTT was shortened. TMS results indicated reduced resting motor threshold (RMT) and central motor conduction time (CMCT), suggesting increased cortical excitability and enhanced synaptic plasticity. Both EEG and MRI showed increases in activation and functional connectivity in the targeted brain regions, implying improved synchronisation of neural networks. These findings suggest that 40Hz multi-target tACS, when applied as an adjunct to intensive rehabilitation, may be a promising approach for alleviating PSCI.